Optimising Young Women’s Suit Pattern and Pressure Comfort (Journal of Fiber Bioengineering and Informatics, 2025)
The comfort of wearing suits, a staple of formal attire, is crucial for the human body. Studies and surveysindicate that individuals often experience discomfort and shoulder pain due to ill-fitting suits, leading touneven pressure distribution and subsequent fatigue. Due to the increasing demands of consumers forclothing, the issue of discomfort in the shoulder area of women’s suits requires improvement. However,most research on women’s suits has focused on aesthetic aspects, with little attention given to thepressure comfort of the shoulder region. This study bridges this gap by examining pattern optimisationand pressure comfort in women’s suits. The study uses Martin’s measuring instruments and 3D scanningto gather shoulder data from young women. The goal is to understand the typical shape and structure ofhuman shoulders. With this information, we develop a method to optimise shoulder patterns in clothing,ensuring they can be adapted to fit different shoulder types comfortably. The research identifies therelationship between the shoulder slope angles of suit patterns and human shoulder shapes, formulatingan equation to link body morphology with pattern design. This study can facilitate designers’understanding of the relationship between human shoulder morphology and clothing patterns, therebyenabling the creation of more comfortable women’s suits for consumers.